Alternative special and differential arrangements for small economies - Davenport, Michael (Commonwealth Secretariat LondonGB, 2002)
Looks at the possibilities of special and differential treatment based on de minimis threshold shares in world trade, both in terms of preferential market access and in terms of derogations from particular WTO disciplines.